Stress distributions for blunt cracks and radiused slits in anisotropic plates under in-plane loadings. (15th March 2015) - Zappalorto, Michele; Carraro, Paolo Andrea
Abstract: An analytical solution for the in-plane stress fields in composite anisotropic plates with blunt cracks is derived using Lekhnitskii's approach. The orthotropic behaviour is obtained as a special case of the more general anisotropic solution. Theoretical predictions are compared to results from a bulk of finite element analyses carried out on tensioned plates with parabolic and U-shaped notches, showing a very satisfactory agreement.